The Ulnar Nerve Sensory and Motor Conduction Studies - Gentili, Giuliano; Di Napoli, Mario (Springer International Publishing : Imprint: Springer, 2016)
This book systematically reviews sensory and motor nerve conduction studies on the ulnar nerve, from pilot human studies of peripheral nerve conduction in the 1950s through to the most recent scientific evidence. Precise descriptions are provided of approx. 70 nerve conduction techniques that were reproduced in the laboratory, with organization of the techniques according to practical criteria for ease of reference. Particular attention is devoted to those techniques that have shown higher sensitivity and specificity in diagnosis of compressive mononeuropathies, such as ulnar neuropathy at the elbow or wrist. Normal and pathological values derived from the original articles and the subsequent literature are presented, and the wealth of illustrative material facilitates comprehension and reproduction of each technique. The volume is completed by a detailed, well-illustrated glossary explaining the more commonly used terms in electrodiagnostic medicine. This book will appeal to novice and experienced neurologists, students, clinical neurophysiology technicians, and rehabilitation physicians. It represents a logical extension of the volumes on the median nerve published by Springer.